2021
DOI: 10.1038/s41598-020-79499-1
|View full text |Cite
|
Sign up to set email alerts
|

Associating cryptogenic ischemic stroke in the young with cardiovascular risk factor phenotypes

Abstract: Acute Ischemic Stroke (AIS) in the young is increasing in prevalence and the largest subtype within this cohort is cryptogenic. To curb this trend, new ways of defining cryptogenic stroke and associated risk factors are needed. We aimed to gain insights into the presence or absence of cardiovascular risk factors in cases of cryptogenic stroke. We conducted a retrospective cohort study of patients aged 18–49 who presented to an urban tertiary care center with AIS. We manually collected predefined demographic, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Possible underlying mechanisms that we assume include: formation of a thrombus on the left atrial side of the aneurysm, or development of interatrial fenestrations that led to a right to left shunt. Hypertension has been associated with cryptogenic stroke; hence we assume that it also contributed to the aetiology of the cryptogenic stroke in our patient [9]. Our case highlights the importance of atrial septum aneurysm as a possible risk factor for cryptogenic ischemic strokes.…”
Section: Discussionsupporting
confidence: 51%
“…Possible underlying mechanisms that we assume include: formation of a thrombus on the left atrial side of the aneurysm, or development of interatrial fenestrations that led to a right to left shunt. Hypertension has been associated with cryptogenic stroke; hence we assume that it also contributed to the aetiology of the cryptogenic stroke in our patient [9]. Our case highlights the importance of atrial septum aneurysm as a possible risk factor for cryptogenic ischemic strokes.…”
Section: Discussionsupporting
confidence: 51%
“…In approximately 40% of young stroke survivors, the cause of stoke is deemed as cryptogenic, indicating that no cause can be identi ed, despite extensive investigation [7,12]. The young stroke survivors in this study who were not able to identify the cause of their stroke did not feel buoyed by the belief they could address their needs into the future and prevent further risk of stroke.…”
Section: Discussionmentioning
confidence: 91%
“…Particularly as young people are less likely to exhibit standard risk factors [1,3] and are more likely to exhibit an atypical stroke phenotype [4,6]. In up to 40% of young people affected by stroke, no cause will be identitied -this is referred to as cryptogenic stroke which can be associated with increased fear of future strokes [7]. Thus younger people are less likely to receive the critical intervention needed in the event of a stroke and may face risks of future strokes [4,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Etiology and risk factors [45,80,82,98,[104][105][106][107][108][109][110][111][112][113][114][115][116][117] FHS was consistently associated with small vessel disease [80,82,[104][105][106][107][108] and large vessel disease [80,98,[105][106][107][108], but not with cardioembolic etiology [45,116,117].…”
Section: Parameter Publications Correlationmentioning
confidence: 99%
“…With regards to stroke etiology, authors consistently reported an association of FHS with small vessel disease [80,82,[104][105][106][107][108], subclinical lacunes [109,110], intracranial artery stenosis [111][112][113][114][115] and large vessel disease [80,98,[105][106][107][108], but not with cardioembolic stroke [45,116,117]. One paper found that FHS was related to lacunar stroke in older subjects and cryptogenic etiology in the younger [118].…”
Section: Type Of Stroke Etiology and Interaction With Risk Factorsmentioning
confidence: 99%